Metal Complexes of Curcumin: A Comprehensive Approach to Design, Synthesis, Characterization and Assessment of Anti-tubercular Activity - Das, Paramita; Yamuna, HM; Harshashree, M; Dang, Raman (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The primary challenge facing Tuberculosis (TB) is the growing prevalence of drug resistance and the hepatotoxicity secondary effects of first and second-line anti-TB treatments have reignited interest in exploring new metal drug complexes as possible sources of anti-TB medications. Aim To perform in silico studies for Curcumin-metal complexes, synthesis and evaluate their antitubercular activity and cytotoxicity. Materials and Methods Designed metal complexes were docked against 2NSD and performed ADMET studies. Based on binding affinity, a series of Curcumin-metal complexes were synthesized, characterized by IR, NMR, MASS, P-XRD and the antitubercular activity was evaluated by MABA and MTT assay for cytotoxicity investigations. Results and Discussion The binding energies ranged from -8.0 to -10.1 ‘kcal/mol’. At -10.1 ‘kcal/ mol’, the Curcumin-Cu complex (C1) exhibited the best binding. The synthesized compounds was evaluated against Mycobacterium tuberculosis (H37Rv) using the MABA assay. Curcumin-Cu complex (C1) showed the highest activity and was the most sensitive at 0.8 µg/mL and showed less toxicity with an IC50 of 10.0 and a selectivity index of 4.0. Cytotoxicity was evaluated by the ATCC CCL-81 cell line. Conclusion Therefore, we can conclude that the molecular hit will be a good lead to develop novel therapies for tuberculosis treatment.
Keywords: Tuberculosis; Curcumin metal complex; Docking; ADMET studies; MABA assay